2014
DOI: 10.1002/stem.1733
|View full text |Cite
|
Sign up to set email alerts
|

NFI-C Regulates Osteoblast Differentiation via Control of Osterix Expression

Abstract: In bone marrow, bone marrow stromal cells (BMSCs) have the capacity to differentiate into osteoblasts and adipocytes. Age-related osteoporosis is associated with a reciprocal decrease of osteogenesis and an increase of adipogenesis in bone marrow. In this study, we demonstrate that disruption of nuclear factor I-C (NFI-C) impairs osteoblast differentiation and bone formation, and increases bone marrow adipocytes. Interestingly, NFI-C controls postnatal bone formation but does not influence prenatal bone develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 39 publications
(50 reference statements)
7
51
1
Order By: Relevance
“…It implies that miR-143 and miR-145 regulated Klf4 and Dsp via the control of Nfic, an upstream effector molecule of Klf4. Furthermore, we have shown that Nfic directly regulates Osx expression but acts downstream of the BMP2-Runx2 pathway in osteoblasts (30). These findings suggest that miR-143 and miR-145 also regulates odontoblast differentiation via the miR-143/145-NficKlf4/Osx-Dspp pathway.…”
Section: Discussionmentioning
confidence: 70%
“…It implies that miR-143 and miR-145 regulated Klf4 and Dsp via the control of Nfic, an upstream effector molecule of Klf4. Furthermore, we have shown that Nfic directly regulates Osx expression but acts downstream of the BMP2-Runx2 pathway in osteoblasts (30). These findings suggest that miR-143 and miR-145 also regulates odontoblast differentiation via the miR-143/145-NficKlf4/Osx-Dspp pathway.…”
Section: Discussionmentioning
confidence: 70%
“…The results confirmed that Nfic promoter had a binding motif for RUNX2, and RUNX2 directly bound to that site in vitro . An in vivo study showed that Nfic expression decreased through BMP-2 pathway in Runx2 -/- mice66. Results from in vivo and in vitro studies demonstrated that Runx2 acts as an upstream regulator of Nfic .…”
Section: Function Of Nfic In Osteogenesismentioning
confidence: 99%
“…Indeed, compound heterozygous Pkd1 +/− ; Runx2 +/− mice that show additive effects to reduce bone mass, implicate Runx2 in a common pathway with PC1 [67]. Complementary in vitro studies suggest that flow induced activation the PC1-PC2 complex regulates Runx2 gene transcription through intracellular calcium and nuclear factor 1 (NFI) family of transcription proteins [67], of which Nfic has been shown to plan an essential role in inversely regulating osteoblast differentiation and bone marrow adipogenesis [169, 170]. …”
Section: Integration Of Mechanosensing Signaling Pathways To Regulamentioning
confidence: 99%